Lithic Raw Material Diversities from Early and Middle Mesolithic northern Norway: A comparative study of sites in Nordland and southern Troms - Seljeås, Pia (UiT Norges arktiske universitet, 2023)
This thesis maps the raw material trends of early and middle Mesolithic Nordland and southern Troms County, northern Norway. The lithics which were procured, used, and discarded makes up substantial parts of the archaeological empirical material. During the last few decades, commercial and infrastructural excavations has increased in numbers in these regions. The findings of these excavations have not been accumulated and cross-examined in a larger sense. This study aims to map the lithic compositions and geographical locations of 25 early and middle Mesolithic sites, excavated between the years of 1974 to 2022. Based on the findings from these 25 sites, the Mesolithic modes of mobility and settlement patterns are reviewed. The raw material trends of early and middle Mesolithic northern Norway were diverse in the meaning of raw material choice. The utilization of the microcrystalline lithic flint was extensive in these regions, located far away from the bedrocks containing flint in southern Scandinavia and on the British Isles. This study maps out a new and thorough interpretation of the preconditions determining flint beach deposits along the coasts of northern Norway. The ‘issue’ of flint beach deposits has not been subject to extensive archaeological or geological inquiry in northern Norway, and by mapping out a plausible hypothesis, this issue is investigated.